2020
DOI: 10.1063/5.0006220
|View full text |Cite
|
Sign up to set email alerts
|

Multi-modal surface analysis of porous films under operando conditions

Abstract: Practical catalysts with a porous framework, such as zeolites, host catalytic reactions at active sites engrained in the pores and channels of the scaffold. The mechanism of interaction at these active sites, defining catalyst performance, remains elusive, in large part, due to the lack of surface characterization methods available for thick films or powders. Here, we present thin film analogs of practical catalysts that allow for the implementation of surface characterization tools, including advanced microsc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
33
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

6
2

Authors

Journals

citations
Cited by 25 publications
(34 citation statements)
references
References 68 publications
1
33
0
Order By: Relevance
“…The rigid shift is likely a consequence of new dipole interactions in the presence of CO adsorbates at the Pd surface. Our previous study showed an analogous shift of Si 2p when investigating the CO adsorption on Pd(111) under 2D silica [47] . Additionally, a report by Yao et al [19] .…”
Section: Resultssupporting
confidence: 53%
“…The rigid shift is likely a consequence of new dipole interactions in the presence of CO adsorbates at the Pd surface. Our previous study showed an analogous shift of Si 2p when investigating the CO adsorption on Pd(111) under 2D silica [47] . Additionally, a report by Yao et al [19] .…”
Section: Resultssupporting
confidence: 53%
“…The system was equipped with a VERTEX 80v FTIR spectrometer with an external MCT detector, and the entire IR beam path was in vacuum. Details of this instrument have been described previously . The instrument was equipped with a polarizer that allowed recording a background with s -polarized light (parallel to the surface plane), while p -polarized light (normal to the surface plane) was used to record the sample spectra.…”
Section: Methodsmentioning
confidence: 99%
“…Details of this instrument have been described previously. 33 The instrument was equipped with a polarizer that allowed recording a background with s-polarized light (parallel to the surface plane), while p-polarized light (normal to the surface plane) was used to record the sample spectra. A Pt(111) single crystal (hat-shaped, 2 mm thick, with a top diameter of 8 mm, from Princeton Scientific Corporation) was initially cleaned by Ar + sputtering and annealing cycles.…”
Section: Methodsmentioning
confidence: 99%
“…XPS experiments were performed at the Center for Functional Nanomaterials at Brookhaven National Laboratory. Both sample preparation and XPS measurements were performed in a lab-based ambient pressure photoelectron spectrometer 32 by SPECS Surface Nano Analysis GmbH, with PHOIBOS 150 NAP hemispherical analyzer. The system has a sample preparation chamber and an analysis chamber separated by a gate valve; the base pressure in the analysis chamber is <10 −9 mbar.…”
Section: ■ Experimental Methodsmentioning
confidence: 99%